Development of a Culturally Grounded Trauma Assessment Protocol in the Middle Eastern Context - Luthfiah Mawar; M. Agung Rahmadi; Luthfiyah Aqilah Siagian; Sasa Maghfirah Siregar; Andieni Pratiwi; Helsa Nasution; Nurzahara Sihombing; Annisa Ardianti Br Tarigan (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study systematically evaluates and develops a trauma assessment protocol based on local cultural contexts through a review and meta-analysis of 87 studies published between 2000 and 2023. Using JASP 0.16.1 and Comprehensive Meta-Analysis V3, results revealed a significant effect size (d = 0.78, 95% CI [0.65, 0.91], p < 0.001), indicating that culturally grounded protocols are more valid than conventional ones. Meta-regression analysis showed that cultural sensitivity accounted for 42.3% of improvements in diagnostic accuracy (β = 0.423, SE = 0.089, p < 0.001), highlighting the importance of cross-cultural understanding in assessment design. Moderator analysis identified three key factors influencing protocol effectiveness: knowledge of local cultural contexts (Q = 24.31, df = 3, p < 0.001), use of culturally appropriate language (Q = 18.76, df = 2, p < 0.001), and involvement of community leaders (Q = 15.92, df = 2, p < 0.001). The study’s heterogeneity was moderate (I² = 68.5%, τ² = 0.142), reflecting variations in implementation. These findings build on prior work by Alarcón et al. (2009) and Jackson et al. (2017), reinforcing the importance of integrating cultural values into trauma assessments. The results demonstrate a more adaptive, systematic framework with significant improvements in predictive validity (AUC = 0.89 compared to 0.76 in non-cultural protocols). This meta-analysis contributes significantly to developing trauma assessment protocols that are more culturally responsive, offering strong empirical evidence for integrating cultural elements into clinical practice.